Potential of the Essential Oil from Pimenta Pseudocaryophyllus as an Antimicrobial Agent - Suzuki Érika Yoko; Baptista Edilene Bolutari; Resende Do Carmo Antônio Márcio; Miranda Chaves Maria Das Graças Afonso; Chicourel Elizabeth Lemos; Barbosa Raposo Nádia Rezende (Acta Pharmaceutica)
This study evaluated the effectiveness of the essential oil of Pimenta pseudocaryophyllus in inhibiting the growth of the main bacteria responsible for bad perspiration odor (Staphylococcus epidermidis, Proteus hauseri, Micrococcus yunnanensis and Corynebacterium xerosis). The chemical profile of the essential oil was evaluated by high-resolution gas chromatography (HR-GC) and four constituents were identified, eugenol being the major component (88.6 %). The antimicrobial activity was evaluated by means of the turbidimetric method, using the microdilution assay. The minimum inhibitory concentration (MIC) values of the essential oil ranged from 500 to 1,000 μg mL-1. Scanning electron microscope (SEM) observations confirmed the physical damage and morphological alteration of the test bacteria treated with the essential oil, reference drugs and eugenol. The findings of the study demonstrated that this essential oil can be used in the formulation of personal care products.